HAKIKAT MANUSIA DAN IMPLIKASINYA TERHADAP PENDIDIKAN ISLAM - Diva Maharani , Annisa; Aulia Ramadani, Syifa; Mahrani, Dani; Gusmaneli, Gusmaneli (CV. ADIBA AISHA AMIRA, 2024)
This article delves into the essence of human beings in Islam by referencing Quranic verses that depict the spiritual, intellectual, and social dimensions of humanity. This essence encompasses the role of humans as stewards on Earth, the innate nature (fitrah) recognizing the oneness of Allah, and the trials and responsibilities that come with free will. The implications of the essence of humanity on Islamic education are underscored through Quranic verses, such as education as character formation (Al-Baqarah 2:197), nurturing the fitrah (Ar-Rum 30:30), and the responsibility as stewards (Al-Baqarah 2:205). Islamic education goes beyond the transmission of religious knowledge; it involves instilling moral values, faith, and piety to shape a generation of noble character. By understanding the essence of humanity in Islam, education is directed towards creating individuals who are not only intellectually astute but also responsible stewards capable of fulfilling their role in maintaining balance on Earth. This article asserts that Islamic education plays a vital role in producing a generation that positively contributes to society and the environment, in accordance with the holistic teachings of Islam.